Aplikasi Smart Investment Planner Berbasis Web - Prasetya K.; Endah K.; Fredicia Fredicia (Bina Nusantara University, 2015)
The lack of knowledge of investment products lead many people decided not to invest for their future. This can be overcome by utilizing the information and communication technology development by making a web application of Smart Investment Planner with the aim to recognize various types of investment product as well as the character investment and tips for users. This application uses a set of data as knowledge base which obtained from the literature, discussions with economic experts, database design, user interface design, as well as tests and evaluations by experts. The result of these applications concluded that this application collect the information as well as investment products that suit into their needs and also encourage them to start invest.